HRM and job performance incentives - Mahy, Benoit; Plasman, Robert; Rycx, Francois (International journal of manpower, 2005)
The 88th Applied Economics Asociation Conference was organized with the specific aim of stimulating discussion on the "Econometrics of Labor Demand". Various sessions have in particular focused in HRM and Job Performance Incentives. The collection of papers in this e-book, originally presented at the conference, provides new evidence on this topic